2016
DOI: 10.1016/j.scitotenv.2016.03.196
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in private well water part 1 of 3: Impact of the New Jersey Private Well Testing Act on household testing and mitigation behavior

Abstract: Regularly ingesting water with elevated arsenic increases adverse health risks. Since September 2002, the NJ Private Well Testing Act (PWTA) has required testing untreated well water for arsenic during real estate transactions in 12 counties. Its implementation provides an opportunity to investigate the effects of policy intervention on well testing and treatment behavior. Here we analyze results of a survey mailed to 1,943 random addresses (37% response), including responses from 502 private well households w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(85 citation statements)
references
References 27 publications
3
82
0
Order By: Relevance
“…27 Overall testing rates were also lower compared to recent studies which found average lifetime testing rates were above 70% in New Jersey and as high as 89% in Maine. 10, 14, 15, 28 Five year testing rates (41%) were also comparable to testing rates from studies of target populations in communities at high risk of arsenic exposure in Wisconsin (41%) 27 and Maine (37%) as well as general Wisconsin population estimates from the Wisconsin Department of Health Services (38%). 29 Rates of testing for common groundwater constituents of concern in the Wisconsin including arsenic and uranium were particularly low and reported by less than 2% of users.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…27 Overall testing rates were also lower compared to recent studies which found average lifetime testing rates were above 70% in New Jersey and as high as 89% in Maine. 10, 14, 15, 28 Five year testing rates (41%) were also comparable to testing rates from studies of target populations in communities at high risk of arsenic exposure in Wisconsin (41%) 27 and Maine (37%) as well as general Wisconsin population estimates from the Wisconsin Department of Health Services (38%). 29 Rates of testing for common groundwater constituents of concern in the Wisconsin including arsenic and uranium were particularly low and reported by less than 2% of users.…”
Section: Discussionsupporting
confidence: 60%
“…Testing programs like those in Oregon and New Jersey can serve as potential important opportunities for both education and surveillance of well water quality and promotion of stewardship. 14, 20 A recent analysis of statewide programs requiring private well testing at the time of real-estate transactions have found testing rates to increase after policy implementation. 14 A desire for knowledge about water quality and safety when there were children or pregnant women in the home also relates to risk perceptions and was ranked as the third reason for testing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations